Repair and Test Method Discussion of Drum Filter Worm Gearbox Driving Device - Gao Lihong; Li Bin; Peng Jian; Wang Zhenshan; Yang Pengliang (Jixie chuandong)
Abstract The combination of worm gear box used for drum filter drive device is a precedent for nuclear power plants in China. By mapping the combination of old worm gearbox used for drum filter drive device,the repair scheme is formulated,different experiments are performed in different ways,the test results meet the requirements. The experience in the repair and test data are summarized,a reference for formulating acceptance specification of nuclear power plant repair is provided,for this purpose,the special test bench is built,a domestic blank is filled.